Carbon origami: A method to fabricate lightweight carbon cellular materials. (July 2018) - Islam, Monsur; Flach, Joshua; Martinez-Duarte, Rodrigo
Abstract: We present the fabrication of lightweight cellular carbon materials using an origami-inspired technique. Complex, porous shapes are fabricated by carbonizing an origami structure made by pre-creasing and manual folding a flat piece of pure cellulosic paper. This relatively simple process yields carbon origami shapes that feature density as low as 0.014 ± 0.005 g/cm 3, 0.93% the density of bulk glassy carbon. Yet, the specific stiffness of this carbon origami and its capability to transfer load compare advantageously to other lightweight cellular materials such as carbon nanotube foams, graphene elastomers, metallic microlattices, silica aerogel, and carbon foams. Such promising mechanical properties coupled to the high temperature resistance and excellent chemical and electrochemical stability of carbon positions carbon origami as a candidate to fabricate lightweight, multifunctional materials.